Associação entre variáveis geográficas e climáticas e a ocorrência de Lutzomya longipalpis (Lutz & Neiva, 1912) (Diptera, Psychodidae, Phlebotominae) no estado do Espírito Santo, Brasil - Pinto, Israel de Souza (2009)
Lutzomyia longipalpis (Lutz & Neiva, 1912) (Diptera, Psychodidae, Phlebotominae) is the main vector of American visceral leishmaniasis (AVL) in Brazil. In the Espírito Santo state, the AVL has always been associated to dry regions and elevations lower than 500 meters at sea level. To infer the potential distribution of L. longipalpis and the influence of biogeographic variables on its potential distribution in Espírito Santo, sand flies were captured on localities with autochthonous cases of AVL and adjacent areas from north region of the state. L. longipalpis was found in 84 localities, for a total of 133 localities belonging to 15 municipalities surveyed. To delimit the potential distribution, it was made ecological niche modeling using the DesktopGarp program and data of 73 occurrence points of L. longipalpis. Besides of the 15 municipalities with records of L. longipalpis, the distribution was provided by ecological niche modeling for, at least, other nine municipalities without records. Yet, the ecological niche modeling showed the association of L. longipalpis with geoclimatic features favorable to its occurrence like as dry climate represented by rainfall lower than 1000 millimeters and elevations lower than 500 meters at sea level. The occurrence of human autochthonous cases of AVL in two localities of Vargem Alta and Rio Novo do Sul municipalities, located on the south portion of ES and without geographic and climatic features favorable to occurrence of L. longipalpis, justified a systematic study for sand flies captured in these localities. From August 2006 to July 2007, mensal systematic entomological surveys were performed in Vargem Alta and Rio Novo do Sul municipalities, but no L. longipalpis was found. Therefore, it is possible that the ocurrence of AVL is disassociated with the presence of L. longipalpis in the south portion of ES. Furthermore, due to the low number of sand flies captured in Rio Novo do Sul, the presence of another mechanism of transmission of AVL is also possible. In conclusion, the presence of L. longipalpis in the Espírito Santo state was associated with geoclimatic well defined features and the occurrence of AVL in areas without these features possibly was related to other mechanism of transmission.